Digital Distraction in Quranic Education: A Mixed Methods Approach - Abdelazeez, Samy; Obeid, Abdul Rahman; Lukman, Muhammad; Alhussian, Hitham; Aziz, Norshakirah; Patel, Ahmed (Khalifa Journal of Islamic Education, 2024)
The increasing popularity of social media has raised concerns about its potential impact on cognitive tasks, including Quran memorization (hifz). While previous studies have explored the effects of digital distractions on learning and memory retention, limited research has specifically examined the relationship between social media usage and Quran memorization. This study addresses this gap by investigating how daily social media consumption influences memorization progress and perceived effectiveness. A survey was conducted among Quran memorizers to assess their social media usage patterns and their correlation with memorization levels. A Kruskal-Wallis test was applied to determine whether significant differences exist in memorization levels across varying social media usage groups. The statistical results indicated no significant association between time spent on social media and memorization levels. However, qualitative responses suggested that excessive social media use negatively affects focus, discipline, and consistency in memorization. These findings highlight the complications of social media’s impact on Quran memorization. While quantitative results did not establish a direct relationship, qualitative insights emphasize the importance of a balanced social media usage for Quran memorization. Future research should build on these findings with larger samples and refined methodologies to bridge the gap between statistical trends and lived experiences.